Exploring the drivers of Forest Management Certification in Malaysia - Murughan, M.; Mohamad Roslan, M. K.; Johar, M.; Zubaidah, H.; Seca, G.; Pakhriazad, H. Z. (Forest Research Institute Malaysia, 2026)
Malaysia has adopted the Malaysian Timber Certification Scheme and the Programme for the Endorsement of Forest Certification (MTCS/PEFC) Forest Management Certification (FMC) to ensure the forest and forest products are managed sustainably and legally since the 2000s. Although the MTCS/PEFC FMC has been practised in Malaysia for more than two decades, the uptake of the MTCS/PEFC FMC remains relatively low. As of 2022, 53% of natural forests and 16% of plantation forests were certified under the MTCS/PEFC FMC. Thus, this study explores the drivers of adopting the MTCS/PEFC FMC. The face-to-face semi-structured interviews were conducted with 15 MTCS/PEFC FMC valid certificate holders from Peninsular, Sabah and Sarawak. The findings revealed that the six drivers, namely market, signalling, legal, incentive, moral and learning, have been significant drivers in adopting and maintaining the MTCS/PEFC FMC. These findings could contribute to policymaking that encourages further adoption of the MTCS/PEFC FMC.